Anorexia Nervosa and Obesity: A Psychological Health Comparison - Berit Hansson; Suzanna Lundblad; JS Torgerson; AK Lindroos; Trevor Archer (Archives of Depression and Anxiety - Peertechz Publications, 2016)
The aim of this pilot study was to compare psychopathological features and psychological health  between women presenting anorexia nervosa (AN) and those presenting obesity (OB). Six AN patients (Body  mass index:  BMI  <15)  and  six OB patients (BMI  >40)  completed  Minnesota Multiphasic Personality Inventory-2 (MMPI-2), Toronto Alexithymia Scale (TAS-20), Beck Depression Inventory  (BDI), the  Symptom  Checklist-90  (SCL-90) and the Eating Disorder  Inventory  (EDI- 2).  These instruments are  self-administered questionnaires for adults. The women also provided information on their global  functioning  (GAF), according to DSM-IV,  through  a  clinical  interview. The AN patients expressed significantly more alexithymic symptoms (TAS-20), more psychological symptoms on the EDI-2 sub-scales, and lower global functioning (GAF) than the OB patients. There were no differences in depression rating or general psychopathology as measured by the BDI, SCL- 90 or MMPI-2. The present results depict certain indications that the psychological health of the AN  patients was more compromised than it was among the OB patients.